Health related quality of life in patients with rheumatoid arthritis from Medellín-Colombia, 2014 (2023)
Rheumatoid arthritis affects the health related quality of life (HRQOL); the HRQOL complements clinical evaluation and is explained by multiple clinical and sociodemographic factors.